The influence of multimodal connectedness on political participation in China: an empirical study of the O-S-R-O-R model based on the life span perspective - Li, Mengyu; Li, Xiaobing (Frontiers in Communication, 2024)
Promoting the construction of Internet democratic politics in China requires understanding how multimodal connectedness can enhance citizens' political participation. This study introduces the O-S-R-O-R (Orientations-Stimuli-Reasoning-Orientations-Responses) model, explaining the pathway from multimodal connectedness to political participation through "multimodal connectedness-political news attention/political news use-interpersonal political discussion-political trust-political participation." Analyzing data from 2379 participants in the context of Internet democratic politics, the study finds that the mediating variables fully mediate the relationship between multimodal connectedness and political participation. While political news attention promotes political participation, political trust has a significant negative impact. The study also compares the model across three age groups:young (18-29 years), middle-aged (30-39 years), and elderly (40-60 years). For the young and middle-aged groups, political news attention negatively impacts political participation, likely due to the fragmentation and distraction caused by real-time messages. Among the elderly, political trust negatively affects political participation, indicating a complex scenario where they are passionate about politics but lack adequate participation channels.